Competitive Advantage through Operational Excellence in Manufacturing - Ng, Choon Hoe (2008)
SIPLACE Center Asia (SCA) is an original equipment manufacturer for surface mounted technology placement machine. It has been ranked in the top three positions of the global market for the past decade. But in recent years, many competitors are putting a fierce fight for bigger piece of the global market share. The sales volume of SIPLACE placement machines has been declining and thus profits are decreasing at an alarming rate. It is known that SIPLACE products are more expensive compared to other competitors. Despite promoting higher performance and better quality, pricing has a big impact on customerÃÂÃÂ¢ÃÂÃÂÃÂÃÂs decision. Therefore the growth strategy has been revised to focus on cost leadership so that better pricing can be offer to customers and hopefully to regain back market share.